Studying the Origin of The Topography of The Ancient Cities of The Ferghana Valley - Karimova Nazokat Vohijon kizi (American Journal Of Social Sciences And Humanity Research, 2026)
Humanity has continued to evolve since its inception. However, there are various debates about the causes of the emergence and development of the first cities. Without cities and the process of urbanization, it is impossible to imagine the next stage of human development. The development of rural and urban areas is one of the most important factors in the advancement of society. Urban planning and the development of urbanization bring a number of challenges to humanity. Globally, the process of urbanization has not been uniform. For example, the Sumerians and Akkadians, the state of ancient Babylon, and the states of Ancient India developed in the 4th and 3rd millennia BCE. In contrast, in the Ferghana Valley, it is assumed that the process of urbanization began in the Bronze Age.